PESAN MORAL DALAM FILM ANIMASI WALL-E - Novieta, Enda Novieta; Rahman, Elmustian Rahman; Sinaga, Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research explains about moral messages in the animation movie Wall-E. The research aims at describing moral messages which are caused by characters toward themselves, characters toward other characters and characters toward their creator. The research uses qualitative approach and descriptive method that aims at describing the moral message in every character in the animation movie Wall-E. The result of the research is classifications of moral messages which are found in the animation movie Wall-E. Theresult of this study also as a from of moral message documentation which is contained in the animation movie Wall-E. The research data was obtained by using observe record technique. Based on the data analysis, it was known that the moral message related to the character attitude toward oneself was 6 data, the moral message related to the character attitude toward the other character was 18 data, and moral message related to the character attitude toward its creator (God) was 1 data. The researcher obtained the total of the whole data was 25 data. Keywords: Moral messages, characters, the animation movie Wall-E.